Exploring minimally invasive approach to define stages of type 1 diabetes remotely - Kontola, Helena (My University, 2022)
The purpose of this study was to study the use of continuous glucose monitoring (CGM) in children who have a high lifetime genetic risk for developing type 1 diabetes. We wanted to find out if the different stages of type 1 diabetes could be defined using CGM data. We also wanted more information on the accuracy of CGM during laboratory oral glucose tolerance test (OGTT) and if a home-OGTT could be a safe alternative for laboratory OGTTs. We recruited 49 subjects aged 4-25 and divided them into five different groups based on their glucose metabolism and amount of insulin islet autoantibodies (IAb). The glucose metabolism evaluation was based on previous laboratory OGTTs and the laboratory OGTT which was performed during the study period. All of the subjects had been measured for IAbs prior to this study period. The study period consisted of a sensoring period, laboratory OGTT and a voluntary home-OGTT. The sensor was put on the subjects at least 24 hours before the laboratory OGTT if it was possible. The data from this study was collected into RedCap forms. I participated in the study design, recruiting of the subjects, and placing the sensors for our study subjects. I created the REDCap forms used in this study and participated in collecting the data into the REDCap forms. I also participated in the writing of the manuscript and performed analysis for tables 1. and 2. and made figures 1-4. I also made the supplemental figure 1. and the analysis for it. There were statistically significant differences between the stage 3 and stage 2 subjects from other study groups. Moreover, CGM did not miss any diabetic OGTTs which is an important safety factor in the follow-up of high-risk subjects. Statistically significant differences between autoantibody negative subjects and subjects with one islet autoantibody were not found with this number of subjects. There was also a difference in the time of the peak glucose values during laboratory OGTT. The difference could be caused by physiological or sensor-related time lag. It is also possible that regular OGTT that doesn’t have a 45-minute timepoint misses the peak values and the matter needs to be further investigated. No adverse events related to the sensor were reported during the study period. Home-OGTTs were safely performed and the results were quite similar to the laboratory sensor glucose values. Our conclusion is that CGM could be a good minimally invasive tool for detecting type 1 diabetes as early as possible even before diabetic OGTT.
Keywords: Type 1 diabetes, continuous glucose monitoring, Impaired glucose metabolism, Islet autoantibodies, Oral glucose tolerance test, Presymptomatic type 1 diabetes, Self-monitoring, Stages of type 1 diabetes (T1D) mellitus